Role of Potassium in Reducing Oxidative Damage in Maize under Salt Stress - Suhaib, Muhammad; Ullah, Muhammad Arshad; Zaman, Badar-uz-; Mahmood, Imdad Ali; Mujtaba, Asma; Asadullah, Hafiz Muhammad (Biological Sciences - PJSIR, 2018)